Using Paper Waste and Local Bacterial Isolates to Produce Biomass and Cellulase Enzyme- A Study Waste Recycling - Suhad Dali Abd –Al Hussien1 , Dhafer Fakri Alrawi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aims to isolate the cellulose-degradation bacteria that produce the cellulase enzyme as well as theproduction of SCP protein from Ramadi city soils and to obtain efficient local bacterial isolates in productionand efficient isolation was selected in the production of cellulase enzyme and single cell protein which isBacillus subtillis bacteria tested the efficiency of the isolated isolation to produce the enzyme and single cellprotein. The cell using local media contains the paper waste available in the environment and contaminatedwith it. Initial transactions were made for this paper waste and these factors included (heating to boilingpoint, dilute sulfuric acid and dilute sodium hydroxide). The paper waste used included the white cardboard,yellow cardboard and white paper Which was used as a single source of carbon and energy, after testingthe waste paper used, it was found that the white cardboard treated with heating gave the best production ofthe cellulase enzyme and single-cell protein. The bacterial isolation used showed the best growth and gavethe highest production of the enzyme and the single cell protein at pH 7, while the best temperature for theproduction of the enzyme was 45 ° C. The optimum temperature for the production of the single cell proteinwas 40 ° C. As for the carbon concentration, which is the white cardboard treated with heating, it was betterto produce than Concentration is 2%. As for the production of single cell protein, the highest output atconcentration was 4%. The best bacterial vaccine size for enzyme production was 3 ml / 100 ml medium. Asfor the production of single cell protein, the size of the inoculum gave 1.5 ml / 100 ml the best production.The addition of the organic nitrogen source (urea) gave a clear increase in enzyme production and singlecell protein, and when adding 0.5 g urea / 100 mL medium. Finally, the results showed that the best periodduration to obtain the highest cellulase enzyme production was after 96 hours, while it was found that thebest production of single-cell protein was after 24 hours incubation.